Prevalence of Trachoma in Bauchi State, Nigeria: Results of 20 Local Government Area-Level Surveys. (7th December 2016) - Mpyet, Caleb; Muhammad, Nasiru; Adamu, Mohammed Dantani; Muazu, Habila; Umar, Murtala Muhammad; Abdull, Mohammed; Alada, Joel; Goyol, Musa; Onyebuchi, Uwaezuoke; Olamiju, Francisca; Isiyaku, Sunday; William, Adamani; et al.
ABSTRACT: Purpose : To determine the prevalence of trachomatous inflammation – follicular (TF) and trichiasis in each of the 20 local government areas (LGAs) of Bauchi State, Nigeria. Methods : We undertook a population-based prevalence survey in each LGA in Bauchi State, employing the Global Trachoma Mapping Project methodology. We used a 2-stage, systematic and quasi-random sampling strategy. Using probability proportional to size, we selected 25 clusters, in each of which 25 households were selected by random walk. All residents of selected households 1 year and older were examined for TF, trachomatous inflammation – intense, and trichiasis, using the World Health Organization simplified grading scheme. Results : Only two LGAs in Bauchi State had TF prevalences in 1–9-year-olds over 5%, with none having TF prevalences of 10% or greater. Only one LGA had a trichiasis prevalence in adults below the elimination threshold; all the others had trichiasis at levels suggestive of public health significance. In all 20 LGAs, more than 60% of households were within 1 km of an improved source of water for hygiene. Conclusion : Efforts need to be made in Bauchi State to provide trichiasis surgery in order to avert trachomatous blindness. Water supplies needs to be sustained and good personal hygiene practices assured so that elimination of trachoma as a public health problem will be achieved and sustained.